Hegemony of the "Great Equalizer" and the Fragmentation of Common Sense: A Gramscian Model of Inflated Ambitions for Schooling. Issue 1 (2nd January 2017) - Isseks, Jerald
Abstract : Increasingly over the past 50 years, the mission statement of schooling in dominant US-American discourse has coalesced around a Great Equalizer narrative of education; that is, it has identified schools as the primary means through which individuals can achieve social mobility. In this article, I employ a Gramscian framework to describe how this dominant yet illusory definition of purpose disorients well-intentioned educational actors and often pits them unwittingly against each other. I show that as a result of a false narrative about what schools do for society, a fragmented common sense has arisen amongst teachers, politicians, scholars and activists to the detriment of a collective theory of change. To guard against fragmentation and avert educational actors' consent to a hegemonic social order, I argue that the first step toward collective resistance is acknowledging the limited impact schools have on the socioeconomic layout of society. Accordingly, educational actors hoping to ameliorate inequality must agree upon more realistic—and less tangible—cultural goals for schooling, such as inculcating critical citizenship and fostering civic participation.